The Effect of Inquiry Method Teaching on Students’ Learning Achievements in Chinese History Course: ผลการจัดการเรียนรู้ด้วยเทคนิคสืบสวนสอบสวนที่มีต่อผลสัมฤทธิ์ ทางการเรียนในวิชาประวัติศาสตร์จีน - ประภากร ภูเทพ (Journal of Faculty of Humanities and Social Sciences Thepsatri Rajabhat University, 2018)
The purpose of the research were 1) to investigate the effectiveness of Inquiry Method Teaching affected to students’ learning achievements in Chinese History course. 2) to investigate students’ attitudes towards the model. The participants were 28 third-year students majoring in Chinese, Faculty of Humanities and Social Sciences, Thepsatri Rajabhat University. The purposive sampling was employed to select the students as participants. The instruments used were lesson plans, pre - and post-test and satisfaction questionnaire. Besides, an interactive learning through action method: ILTA integrated with PAOR cycle – P (plan), A (act), O (observe) and R (reflect) was also used as data collection. Then, the data were compared and analyzed. The findings were as follows:1) The overall achievement after learning with the investigation instructional model in Chinese History Course was a statistically significant difference at the level of .05. 2) The finding from questionnaire indicated that the students’ satisfaction towards the model was at the highest level (4.63). This reflected that the model improved the students’ understandings of the lessons well.